The proportion of impervious surfaces at the landscape scale structures wild bee assemblages in a densely populated region - Geslin, Benoît; Le Féon, Violette; Folschweiller, Morgane; Flacher, Floriane; Carmignac, David; Motard, Eric; Perret, Samuel; Dajoz, Isabelle (Ecology and evolution, 2016)
Given the predicted expansion of cities throughout the world, understanding the effect of urbanization on bee fauna is a major issue for the conservation of bees. The aim of this study was to understand how urbanization affects wild bee assemblages along a gradient of impervious surfaces and to determine the influence of landscape composition and floral resource availability on these assemblages. We chose 12 sites with a proportion of impervious surfaces (soil covered by parking, roads, and buildings) ranging from 0.06% to 64.31% within a 500 m radius. We collected using pan trapping and estimated the landscape composition of the sites within a 500 m radius and the species richness of plant assemblages within a 200 m radius. We collected 1104 bees from 74 species. The proportion of impervious surfaces at the landscape scale had a negative effect on wild bee abundance and species richness, whereas local flower composition had no effect. Ground‐nesting bees were particularly sensitive to the urbanization gradient. This study provides new evidences of the impact of urbanization on bee assemblages and the proportion of impervious surfaces at the landscape scale emerged as a key factor that drives those assemblages. Wild bee abundance and richness decline with the increase of impervious surfaces. Ground nesting bees are particularly sensitive to urbanization. Local flower composition had here no effect on bees assemblages. Impervious surfaces at a landscape scale are a key factor structuring bee assemblages.